War an enquiry - Grayling, A. C. (Yale University Press, 2017)
In this original and deeply considered book, A. C. Grayling examines, tests, and challenges the concept of war. He proposes that a deeper, more accurate understanding of war may enable us to reduce its frequency, mitigate its horrors, and lessen the burden of its consequences. Grayling explores the long, tragic history of war and how warfare has changed in response to technological advances.